Pengaruh Literasi Keuangan Syariah Terhadap Perilaku Keuangan Pada Mahasiswa Politeknik Negeri Bandung (Studi Pada Mahasiswa Keuangan Syariah Politeknik Negeri Bandung) - Nayla Sandra Aulia; Nafisah Ruhana; Noorsyah Adi Noeridha (Journal of Applied Islamic Economics and Finance, 2023)
This study examines the impact of Islamic financial literacy on financial behavior among Islamic finance students at Politeknik Negeri Bandung. The variables analyzed include Islamic financial literacy (X) and financial behavior (Y). A quantitative descriptive approach was used, and data was collected through a questionnaire distributed via Google Forms. The sample consisted of 256 students from the Islamic Finance Study Program, with a calculated sample size of 156 using the Slovin formula and a 0.05 error rate. The relationship between the variables was analyzed using simple linear regression with SPSS software version 25. The findings reveal that the level of Islamic financial literacy among Politeknik Negeri Bandung students is relatively good, with an average score of 12.5 out of 19. Islamic financial literacy explains 5.6% of financial behavior, while the remaining 94.4% is influenced by other variables beyond the scope of this study. The data analysis resulted in a significance value of 0.002, indicating that Islamic financial literacy has a positive and significant impact on the financial behavior of Islamic Finance Study Program students at Politeknik Negeri Bandung. Keywords: Islamic financial literacy, Islamic financial behaviour